Cross-cultural adaptation of the Impact on Participation and Autonomy questionnaire for Brazil for people with spinal cord injury - Sousa de Andrade, Valeria (2024)
Introduction: People with chronic conditions and/or disabilities can have an impact on their autonomy and participation, impairing their performance in daily activities. The measurement of these constructs should consider the biopsychosocial model. Objective: To cross-culturally adapt the Impact on Participation and Autonomy questionnaire for people with spinal cord injury for use in the Brazilian context. Method: Methodological study carried out in a rehabilitation center of a Brazilian public hospital involving people with spinal cord injury aged 18 and over. Internationally standardized procedures were followed for the translation-backtranslation process and evaluation of the semantic aspects of the questionnaire. Results: The questionnaire was translated by two independent professionals, followed by a synthesis of the translations. The semantic, cultural, idiomatic and conceptual equivalences were then verified by the Expert Committee, followed by back-translation, which was sent to the author of the questionnaire. Eighteen people with spinal cord injury took part in the cognitive debriefing, with an average age of 38.8 years (SD = 13.1). Participants pointed out that the final version was good or very good (n=17), the questions were easy to understand (n=11), with items that are very important for the state of health/illness (n=14) and that there were no difficulties using the response categories (n=11). Conclusion: The Brazilian version of the Impact on Participation and Autonomy questionnaire was easily understood, accepted and considered relevant by the participants. After validation, the questionnaire could be included in the clinical practice of rehabilitating people with spinal cord injury considering biopsychosocial aspects.